2016
DOI: 10.1007/s00221-016-4587-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 6 h of running on brain activity, mood, and cognitive performance

Abstract: Long-duration exercise has been linked with the psychological model of flow. It is expected that the flow experience is characterized by specific changes in cortical activity, especially a transient hypofrontality, which has recently been connected with an increase in cognitive performance post-exercise. Nevertheless, data on neuro-affective and neuro-cognitive effects during prolonged exercise are rare. The cognitive performance, mental state, flow experience, and brain cortical activity of 11 ultramarathon r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 27 publications
1
30
2
2
Order By: Relevance
“…While female ultra-marathoners tend to be more intrinsically motivated (Krouse et al, 2011 ), less concerned with the competitive nature (Frick, 2011 ) and more attentive to health (Krouse et al, 2011 ), men have a competitive nature in which they want to compete with opponents and win a race (Doppelmayr and Molkenthin, 2004 ). Women also have a higher flow experience during an ultra-marathon than men (Wollseiffen et al, 2016 ).…”
Section: Women In the Ultra-marathonmentioning
confidence: 99%
“…While female ultra-marathoners tend to be more intrinsically motivated (Krouse et al, 2011 ), less concerned with the competitive nature (Frick, 2011 ) and more attentive to health (Krouse et al, 2011 ), men have a competitive nature in which they want to compete with opponents and win a race (Doppelmayr and Molkenthin, 2004 ). Women also have a higher flow experience during an ultra-marathon than men (Wollseiffen et al, 2016 ).…”
Section: Women In the Ultra-marathonmentioning
confidence: 99%
“…To date, studies examining contexts for flow in sport have referred to differences between types of sport (e.g., Jackson, Thomas, Marsh, & Smethurst, 2001) or between training and competition (Koehn & Morris, 2014). Recent research has also found that flow tends to occur during the early or middle stages of performance for professional golfers (Swann et al, 2016) and, for example, in the first hour of a 6-hr run for ultramarathon runners (Wollseiffen et al, 2016). Our findings indicate that flow can occur at any time during a performance provided the context is uncertain, is novel, or requires experimentation and the athlete experiences a buildup in confidence.…”
Section: Performance Contextsmentioning
confidence: 99%
“…The duration of exercise was selected for comparison with previous literature (Millet et al, 2000; Vernillo et al, 2015), including a study having measured decreased PFC activity (Wollseiffen et al, 2016), and to correspond to the acute phase of alterations in and C r observed in a previous study (Gimenez et al, 2013). To establish the specific effect of exercise duration, we aimed to measure the selected parameters at a moderate intensity (Gaesser & Poole, 1996) corresponding to the expected average speed of a group of trained ultramarathon runners, and at a heavy exercise intensity (Gaesser & Poole, 1996) minimizing the contribution of eccentric contractions to mechanical work, i.e., uphill (Minetti, Ardigo & Saibene, 1994).…”
Section: Introductionmentioning
confidence: 99%